Abordagens biofísicas e vibracionais na investigação de taupatias e declínio cognitivo associado ao diabetes - AMORIM, Maria do Socorro do Nascimento (2025)
Neurodegenerative diseases, such as tauopathies, pose a growing public health challenge due to their devastating impact on quality of life and the lack of effective treatments. Tauopathies, including Alzheimer’s disease, are characterized by the abnormal aggregation of tau protein, a microtubule-associated protein essential for maintaining neuronal structure and function, leading to neuronal dysfunction and cognitive decline. The connection between these diseases and diabetes mellitus, a metabolic disorder characterized by hyperglycemia, has emerged as an important focus of scientific research. This interrelationship underscores the importance of understanding the molecular and cellular foundations of these conditions to develop effective therapeutic strategies. This study is divided into two parts: (i) a review highlighting the use of Atomic Force Microscopy (AFM) as a suitable research tool for studying cellular damage in tauopathies, even at early stages, which allows for the elucidation of the pathogenic mechanisms underlying these diseases. This section synthesizes recent studies that applied AFM to investigate structural and biophysical changes associated with tauopathies, including Alzheimer’s and Parkinson’s diseases, focusing on the analysis of the mechanical properties of tau aggregates and changes in cellular and tissue morphology. To this end, a literature search was conducted for studies from the past five years that utilized AFM to explore tissues, cells, and proteins in the context of tauopathies, compiling the primary approaches and findings of each study. By integrating and evaluating recent advancements, this work provides a comprehensive view of AFM's crucial role in understanding the molecular mechanisms underlying tauopathies and promoting new approaches to treating these devastating conditions; and (ii) the characterization of ultrastructural, nanomechanical, and vibrational alterations in hyperglycemic hippocampal tissue using Atomic Force Microscopy and Raman Spectroscopy (RS), which investigates how diabetes mellitus contributes to cognitive decline by examining the effects of insulin resistance in the brain on neural function. The results reveal distinct molecular signatures and altered mechanical properties in pathological tissues, offering new insights into the mechanisms underlying neurodegeneration and the impact of diabetes on the brain. By deepening the understanding of these changes, this work contributes to the development of potential biomarkers for diagnostics. paving the way for novel therapeutic strategies targeting tauopathies and their relationship with diabetes mellitus.